Invisible Factors: Strategies for Raising Awareness of Human Factors Among Undergraduate Students. (September 2013) - Brill, J. Christopher; DeLucia, Patricia R.; Flach, John M.; Kaber, David B.; Youmans, Robert J.
The objective of this Education Technical Group (ETG) panel is to discuss the problem of recruiting students into the Human Factors and Ergonomics (HF/E) discipline and to offer strategies and solutions for effectively increasing awareness of HF/E among undergraduate students in psychology and engineering. Each panelist was selected because of his or her experience with and commitment to HF/E education. Drs. J. Christopher Brill, Patricia DeLucia, John Flach, David Kaber, and Robert Youmans will participate in the discussion. Dr. Brill will provide an introduction to frame the discussion and will present effective strategies for increasing undergraduate enrollment in HF/E courses. Dr. DeLucia will provide her perspective on integrating human factors into an undergraduate psychology curriculum. Dr. Flach will discuss how exposing undergraduates to the tangible, design-related aspects of HF/E may increase student interest. Dr. Kaber will discuss the need for increased emphasis on graduate education in Industrial Systems Engineering. Dr. Youmans will present perspectives on how the realities of academia disincentivize faculty members from focusing upon undergraduate student development.